1992
DOI: 10.3109/00016489209137463
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsaicin Desensitization on Nasal Allergy-like Symptoms and Histamine Release in the Nose Induced by Toluene Diisocyanate in Guinea Pigs

Abstract: Intranasal application of toluene diisocyanate (TDI) induced nasal allergy-like symptoms of sneezing and watery rhinorrhea and decreased the histamine content of the nasal mucosa in guinea pigs. However, in the animals pretreated with capsaicin (capsaicin desensitization) before sensitization with TDI, nasal allergy-like symptoms were not induced. Capsaicin desensitization also inhibited histamine release in the nasal mucosa induced by TDI. These findings suggest that antidromic impulses of capsaicin-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…Nasal allergic-like symptom was measured by means of the number of sneezes and the extent of watery rhinorrhea using the method of Abe et al (9). After TDI provocation, animals were placed in a plastic cage (one animal per cage) and the number of sneezes and severity of watery rhinorrhea were examined for 10 min.…”
Section: Evaluation Of Nasal Allergic-like Symptommentioning
confidence: 99%
“…Nasal allergic-like symptom was measured by means of the number of sneezes and the extent of watery rhinorrhea using the method of Abe et al (9). After TDI provocation, animals were placed in a plastic cage (one animal per cage) and the number of sneezes and severity of watery rhinorrhea were examined for 10 min.…”
Section: Evaluation Of Nasal Allergic-like Symptommentioning
confidence: 99%
“…Our previous works (7,8) have demonstrated that repeated intranasal application of toluene 2,4-diisocyanate (TDI) induced release of histamine from mast cells via neurogenic inflammation and leads to the development of nasal hypersensitivity behavior in guinea pigs. We also showed that both H1R mRNA and H1R protein level were up-regulated in TDI sensitized allergic rats and H1R mRNA was significantly suppressed by the treatment of d-chlorpheniramine, an H1R antagonist (9).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that irritation of sensory nerves with certain chemical irritants such as toluene diisocyanate (Takeda et al, 1993;Abe et al, 1992), capsaicin (Gepetti et al, 1988), formaline (Lundblad et al, 1984), and nicotine (Lundblad et al, 1984) induces sneezing, nasal secretion, and nasal congestion. These irritants induce the release of neuropeptides such as substance P (SP), calcitonin gene-related peptide (CGRP), and other neuropeptides from peripheral terminals of the trigeminal nerve Kokumai et al, 1992;.…”
Section: Discussionmentioning
confidence: 99%